Major Fisheries Species along with Their Contribution to the National Fishery Production in Bangladesh - Manik, Mehedi Hasan (Jurnal Perikanan Universitas Gadjah Mada, 2024)
In Bangladesh, due to its geographical location, fisheries play a significant role in socioeconomic development and food security. The country has 57 major rivers and nearly 118,813 km2 marine area in the Bay of Bengal. Almost 260 freshwater and 740 marine water fisheries species are found in Bangladesh. There is a lack of studies dealing with species-wise production status and growth rate in Bangladesh. This study is conducted to discover the recent trend of fisheries yield with major species-wise production share and growth rate. The required data have been collected from the website of the Department of Fisheries of the government of Bangladesh. Fisheries yield is increasing in Bangladesh, but the inland culture segment is growing fast compared to inland capture and marine segments as the slope of inland culture is 1.1, higher than inland capture and marine. Species converging in the major carp group are the highest, over 21%, contributor to the national yield. As a single species, the Hilsa takes the maximum production share, around 12%. The contribution of marine species is poor, approximately 15% of the total yield, compared to the potential. Bangladesh may raise the required export diversification based on fisheries resources. To do so, the policymakers of Bangladesh should raise funds for blue economic research, human resource development, and technology import.